Photoautotrophic System: A Review and Potential Application for Plant Propagation In Vitro - Krisantini Krisantini; Ni Made Armini Wiendi (Department of Agronomy and Horticulture, IPB University, 2018)
AbstractThe standard method of in vitro plant micro propagation uses of tightly closed culture bottles using agar media containing macro and micro nutrients and sucrose as a source of carbon for the explants. The closed bottle culture is usually kept in a temperature and light controlled environment which is lower and of different quality from the natural sunlight, resulting in high relative humidity and no air exchange inside the bottles. Explants produced in vitro have malfunctioned stomata, undeveloped cuticles and lower leaf chlorophyll levels, and hyper hydration of the plantlets. Photoautotrophic tissue culture is micro propagation without or with a reduced sugar level in the culture media, so the growth or accumulation of carbohydrates of the explants is dependent fully upon photosynthesis and inorganic nutrient uptake. This method is usually combined with ventilation or CO2 enrichment, and recently, with incorporating porous materials such as vermiculite, gum or paper pulp to the agar media to promote better root system of the explants. This article discuss the advantages and disadvantages of the photoautotrophic micro propagation compared to the standard micro propagation methods, and provided the results of the photo autotrophic micro propagation studies conducted at Laboratory of Tissue Culture II of the Department of Agronomy and Horticulture, Bogor Agricultural University, Indonesia.